Utilization Of Effective Microorganism Probiotics through Drinking Water To Improve The Slaughter Weight and Carcasses Physical Composition of Male Bali Duck - K. B., Budiyatmika; Siti, N W.; Ardika, I N. (Jurnal Peternakan Tropika, 2019)
The study aimed to determine the effect of giving Effective Microorganism probiotics through drinking water on the slaughter weight and carcasses physical composition of male bali duck.  The research was conducted in Kediri, Tabanan, for 8 weeks starting from August 2 to October 2, 2018..  The design used was a Completely Randomized Design (CRD) consisting of three treatments, namely: A (Drinking water without Effective Microorganism probiotics as a control), B (Drinking water + 0.5% Effective Microorganism probiotics), C (Drinking water + 1% Effective Microorganism probiotics).  Each treatment consisted of five replications and each replication used three male bali ducks aged 3 days with an average body weight ranging from 55,72 ± 7,16 g.  The variables observed were slaughter weight, carcass weight, carcass percentage, bone percentage, meat percentage, and percentage of subcutaneous fat including skin.  The results showed that administration of Effective Microorganism probiotics through drinking water at the level of 1% significantly increased male bali duck weight, but did not significantly increase carcass weight, meat percentage, percentage of subcutaneous fat including skin and not significantly decrease carcass percentage, and bone percentage.  Based on the results of the study it can be concluded that the administration of Effective Microorganism probiotics through drinking water at the level of 1% it can increase the slaughter weight of male bali duck, but at the level of 0,5-1% does not affect the carcasses physical composition of male bali duck.  Keywords: probiotics, male bali duck, carcasses